1995
DOI: 10.1148/radiology.196.1.7784558
|View full text |Cite
|
Sign up to set email alerts
|

Breast MR imaging with commercially available techniques: radiologic-pathologic correlation.

Abstract: Breast MR imaging is a slightly more sensitive modality than mammography but not a highly specific technique for evaluating breast lesions. It has utility in several clinical situations but should not be used as a substitute for biopsy or general screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 0 publications
2
36
1
Order By: Relevance
“…However, many of these lesions were multicentric in presentation. Fobben et al detected similar numbers of cancers with mammography and MRI [9]. Heywang-Ko È brunner detected 27 of the 70 cancers in 525 ªproblem casesº only with MRI [3].…”
Section: Sensitivity Of Enhanced Mri For Detection Of Breast Cancermentioning
confidence: 99%
“…However, many of these lesions were multicentric in presentation. Fobben et al detected similar numbers of cancers with mammography and MRI [9]. Heywang-Ko È brunner detected 27 of the 70 cancers in 525 ªproblem casesº only with MRI [3].…”
Section: Sensitivity Of Enhanced Mri For Detection Of Breast Cancermentioning
confidence: 99%
“…No report on item 11 and item 14 was found in six studies (Fenlon et al 1997;Fischer et al 1999;Alamo et al 2001;Goerres et al 2003;Sardanelli et al 2005;Woodhams et al 2010) and two studies (Fobben et al 1995;Stomper et al 1995) respectively. No report on item 12 was found in six studies (Fobben et al 1995;Fenlon et al 1997;Fischer et al 1999;Alamo et al 2001;Goerres et al 2003;Woodhams et al 2010) and results of "no" in seven studies (Kawashima et al 2001;Knopp et al 2003;Pediconi et al 2005;Sardanelli et al 2005;Kneeshaw et al 2006;Pediconi et al 2008;Martincich et al 2011). The methodological quality of the included trials is shown comprehensively in Table 3.…”
Section: Methodological Quality Of Studiesmentioning
confidence: 97%
“…Because the dosage unit of contrast media can't be translated, that is to say, the absolute difference on dosage among these studies is unknown, 2 articles were rejected. 17 studies (Fobben et al, 1995;Stomper et al, 1995;Fenlon et al, 1997;Helbich et al, 1997;Fischer et al, 1999;Alamo et al, 2001;Kawashima et al, 2001;Goerres et al, 2003;Knopp et al, 2003;Pediconi et al, 2005;Sardanelli et al, 2005;Kneeshaw et al, 2006;Pediconi et al, 2007;Pediconi et al, 2008;Woodhams et al, 2010;Luciani et al, 2011;Martincich et al, 2011) with 1934 patients were included based on the inclusion criteria and the data integrity.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) has a sensitivity in the diagnosis of carcinoma of 86-96% 11,12 and some series of studies have shown sensitivity for DCIS detection using this method ranging from 20 to 95%. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Due to the wide variation observed in sensitivity rates, demonstrating the most common presentations of this condition in Brazilian patients derived from a screening program in a Teaching Hospital is justified.…”
Section: Introductionmentioning
confidence: 99%